(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Studies on fruiting, bearing habit and fruit growth of jackfruit was carried out at orchard of Jackfruit Research Project, Department of Horticulture, Bangladesh Agricultural University (BAU), Mymensingh during the period from November 2000 to October 2001. Ten jackfruit germplasm of 13 years of age were selected for this study. Fruit bearing habit of jackfruit was cauliflorous i.e., fruits are borne on trunk and branches. The germplasm under study bore fruits on trunk, primary, secondary, tertiary, fourth, fifth and sixth branches of jackfruit trees. On an average, the maximum fruits were borne on primary branches (33.0%) followed by those on trunk (31.5%), secondary (12.3%), and fourth branch (8.4%), while it was the lowest on sixth branch (2.0%). The growth pattern of fruit of jackfruit is characterized by single sigmoid curve. This is true when all aspects of measurements viz, length, diameter, circumference, weight, and volume of fruits; length, breadth, weight of bulb as well as seed were plotted against time from fruit set to haiwesting maturity. Key Words: Bearing habit, fruit growth, jackfruit germplasm. doi:10.3329/bjar.v33i3.1598 Bangladesh J. Agril. Res. 33(3) : 391-397, September 2008